2014
DOI: 10.17511/ijmrr.2014.i02.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kangaroo Mother Care on Heart rate, Respiratory rate and Temperature in Low Birth Weight Babies

Abstract: Background: Kangaroo mother care (KMC) involves skin-to-skin positioning of the infant in an upright position against the mother's chest. The two other components of KMC are frequent and exclusive breastfeeding (where possible) and early discharge from hospital. Aim of present study was to asses effect of kangaroo mother care on heart rate, respiration rate and temperature of low-birth weight preterm newborns admitted in a tertiary care centre of central India. Methods: Low birth weight babies (weighing< 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
3
1
1
Order By: Relevance
“…13,14 Similarly, observational studies by Jain PK and Verma P also found insignificant change RR with KMC. 5,17 These findings are inconsistent with the findings of present study.…”
Section: Discussioncontrasting
confidence: 97%
“…13,14 Similarly, observational studies by Jain PK and Verma P also found insignificant change RR with KMC. 5,17 These findings are inconsistent with the findings of present study.…”
Section: Discussioncontrasting
confidence: 97%
“…As well, placing the neonate in upright position, decreases the compression of the diaphragm, maximizes ventilation and perfusion resulting in improved respiratory function. (39) The current study results are consistent with Mohamed et al (2013), who concluded that KMC could effectively, and positively promote premature neonates' biological stability than those cared for by conventional care. (40) Similarly, Sarparast et al (2015) reported that respiratory rate was significantly decreased to more stabilized level during KMC.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, the brain stem shifts from sympathetic control responsible for stress reaction and hyper-alertness to parasympathetic one responsible for relaxation and contentment. (39) Moreover, skin-to-skin contact with mothers is likely to be accompanied by less cry that means less stress, lower levels of cortisol, and more physiological stabilization. As well, placing the neonate in upright position, decreases the compression of the diaphragm, maximizes ventilation and perfusion resulting in improved respiratory function.…”
Section: Discussionmentioning
confidence: 99%
“…We could not nd any study which was done on residents of mothers or attendees (at home) and in secondary care with level 1 NICU facility, coal mines hospital. But we found similar types of studies done in tertiary care hospitals by Pramila Verma et al and they concluded that after KMC there was a mean rise in temperature from 96.69 ± 2.45°F to 98.07 ± 0.41°F which was statistically signi cant (p = < 0.001) [11]. Ludington-Hue SM et al observed in their randomized controlled trial study that after KMC mean temperature remained within clinically acceptable ranges which was statistically signi cant [12].…”
Section: Discussionsupporting
confidence: 87%